Aggregation‐Induced‐Emission Photosensitizer‐Loaded Nano‐Superartificial Dendritic Cells with Directly Presenting Tumor Antigens and Reversed Immunosuppression for Photodynamically Boosted Immunotherapy. Issue 3 (9th December 2022) - Sun, Zhihong; Liu, Jie; Li, Yueying; lin, Xun; Chu, Yongli; Wang, Wenting; Huang, Shiyun; Li, Wei; Peng, Jin; Liu, Chuyao; Cai, Lintao; Deng, Wenbin; et al.
Abstract: The success of tumor immunotherapy highlights the potential of harnessing immune system to fight cancer. Activating both native T cells and exhausted T cells is a critical step for generating effective antitumor immunity, which is determined based on the efficient presentation of tumor antigens and co‐stimulatory signals by antigen‐presenting cells, as well as immunosuppressive reversal. However, strategies for achieving an efficient antigen presentation process and improving the immunosuppressive microenvironment remain unresolved. Here, aggregation‐induced‐emission (AIE) photosensitizer‐loaded nano‐superartificial dendritic cells (saDC@Fs‐NPs) are developed by coating superartificial dendritic cells membranes from genetically engineered 4T1 tumor cells onto nanoaggregates of AIE photosensitizers. The outer cell membranes of saDC@Fs‐NPs are derived from recombinant lentivirus‐infected 4T1 tumor cells in which peptide‐major histocompatibility complex class I, CD86, and anti‐LAG3 antibody are simultaneously anchored. These saDC@Fs‐NPs could directly stimulate T‐cell activation and reverse T‐cell exhaustion for cancer immunotherapy. The inner AIE‐active photosensitizers induce immunogenic cell death to activate dendritic cells and enhance T lymphocyte infiltration by photodynamic therapy, promoting the transformation of "cold tumors" into "hot tumors, " which further boosts immunotherapy efficiency. This work presents a powerful photoactive and artificial antigen‐presenting platform for activating both native T cells and exhausted T cells, as well as facilitating tumor photodynamic immunotherapy. Abstract : Nano‐superartificial dendritic cells (saDC@Fs‐NPs) are developed by coating superartificial dendritic cells membranes onto aggregation‐induced emission (AIE) photosensitizers. The outer cell membranes are derived from engineered 4T1 cells in which pMHC‐I, CD86, and anti‐LAG3 are simultaneously anchored. saDC@Fs‐NPs directly stimulate T‐cell activation and reverse T‐cell exhaustion for cancer immunotherapy. The inner AIE‐active photosensitizers induce immunogenic cell death to improve tumor microenvironment, which boosts immunotherapy efficiency.